Piano teaching and autism spectrum disorder: a systematic review (Orfeu, 2023)
Seeking to understand the relationship between the Piano and Autism Spectrum Disorder (ASD) in order to favor the actions of music educators/piano teachers and contribute to the academic-scientific production in the area of ​​piano pedagogy, this study aimed to investigate through a systematic review of the knowledge produced about piano teaching for autistic people, up to this time.  For this purpose, a search on academic-scientific production was carried out in the following databases CAPES Periodials, Brazilian Theses Bank (BDTD), Brazilian Portal for Open Access to Scientific Information (OasisBr), ResearchGate and Scopus, and in the main Brazilian Periodicals in the field of music. Fifteen works were selected. The review research points to the importance of the teacher knowing diversified teaching strategies and knowing how to adapt them to the student’s limitations and potentialities, always seeking to provide significant musical experiences in learning the instrument.
Keywords: autism spectrum disorder; piano pedagogy; music education